Queer Africa : New and Collected Fiction - Xaba, Makhosazana; Martin, Karen (Book collections on Project MUSE., 2014)
Queer Africa is a collection of unapologetic, tangled, tender, funny, bruising and brilliant stories about the many ways in which we love each other on the continent - In these unafraid stories of intimacy, sweat, betrayal and restless confidences, we accompany characters into cafes, tattoo salons, the barest of bedrooms, coldly gleaming spaces into which the rich withdraw, unlit streets, and their own deepest interiors.